Plasma mineral and biochemical profiles and milk composition alterations with parity in dairy cattle: a study from South Kashmir - Sayima Akhter; Beigh, Yasir Afzal; Abdul Majeed Ganai; Haidar Ali Ahmad (Indian Journal of Dairy Science, 2025)
Mineral deficiency is a region-specific problem with a significant impact on livestock productivity, and can be assessed by measuring blood mineral levels that depends upon the mineral content in available feedstuffs, different abiotic factors and biological conditions including parity. This study aimed to determine the mineral profile of feedstuffs and plasma along with the metabolic parameters and milk composition in dairy cows of different parities under farmers’ field condition in district Shopian of Kashmir division. A total of 201 blood and 156 milk samples were collected randomly from dairy cattle in 6 tehsils of two veterinary blocks (Shopian and Keegam) of the district. These samples were divided into four groups based on parity of animals as: primiparous (Parity 1), multiparous (Parity 2), multiparous (Parity 3), and older multiparous (Parity 4 and above). Also, samples of feeds and fodders most commonly offered to cattle by the dairy farmers were collected separately, pooled tehsil wise and analysed. The chemical composition of the feedstuffs were within prescribed normal ranges, while available fodders were deficit in P, Cu and Zn but the concentrate feeds were adequate in all minerals. All plasma macro-minerals and Fe were above the critical levels across all parities throughout the district; however, deficiency prevalence for Ca, P and Cl (macro-) as well as Cu and Zn (micro-minerals) in plasma were higher (P